EUV lithography - Bakshi, Vivek (SPIE Press ; John Wiley, 2009)
Dr. Bakshi has compiled a thorough, clear reference text covering the important fields of EUV lithography for high-volume manufacturing. This book has resulted from his many years of experience in EUVL development and from teaching this subject to future specialists. The book proceeds from an historical perspective of EUV lithography, through source technology, optics, projection system design, mask, resist, and patterning performance, to cost of ownership. Each section contains worked examples, a comprehensive review of challenges, and relevant citations for those who wish to further investigate the subject matter. Dr. Bakshi succeeds in presenting sometimes unfamiliar material in a very clear manner. This book is also valuable as a teaching tool. It has become an instant classic and far surpasses others in the EUVL field.
Keywords: Ultraviolet radiation -- Industrial applications.; Photolithography.; Optical coatings.; elektronické knihy; electronic books